Herramientas periodísticas usadas en las salas de redacción para comprobación de hechos y verificación - Navarrete Pérez, Gabi Rubí (2020)
This research focused on studying the use of journalistic tools within newsrooms, since currently the immediacy of the information provided by any citizen, competes directly with journalism, thus generating communication professionals to work more fast, which could cause errors in the news spread. To meet this objective, it was necessary to use the deductive, inductive and logical historical methods, through the survey technique aimed at editors of various written media, in order to know the challenges they face in this era digital. The findings of this study were helpful, since they determined the problems journalists face, because they compete for the scoop and the verification and verification of the news. Due to this, it can be concluded that the responsible use of their professional tools is important for communicators, despite living in an era of immediacy, it is understood that the important thing is not who informs first but who informs well.